HAND ANTHROPOMETRY - A VALUABLE PARAMETER FOR GRIP STRENGTH AND HAND FUNCTIONAL ASSESSMENT - Sethi, Ruchira; Jha, Shweta (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to study the relationship between hand length (HL) and hand width with grip strength and writing speed among medical students. This plays a crucial role in evaluating functional ability and motor skills. Methods: This cross-sectional observational study was conducted 255 undergraduate students (M=110, F=145); 18–25 age group was selected for the study. HL, hand width, grip strength, and handwriting speed were measured and correlated. Results: The average measurement for HL was 188.2 mm and 181.43 for right and left hand, respectively. The figures for hand width were 75.59 mm and 75.37 mm for right and left hand, respectively. The average values for grip strength 19.24 kg and 19.25 kg for right and left hand, respectively. Average handwriting speed was 119.6 letters/min. Conclusion: Provides normative data for hand anthropometry, handgrip strength, and handwriting speed in undergraduate medical students. Hand anthropometry correlated significantly with the grip strength. Handwriting speed is accentuated with increase in length as shown in this study.